Analysis of Financial Statement Audit Planning (Case Study at Boy Febrian Public Accounting Firm) - Ananda, Sopia; Putra, Rudi Syaf (Fakultas Ekonomi dan Bisnis Universitas Ibn Khaldun Bogor, 2025)
The purpose of this study was to determine how the audit planning process, documentation during the audit process and see whether the audit planning at KAP Boy Febrian was in accordance with the Public Accountant Professional standards by the Indonesian Institute of Accountants in SPAP. The research was conducted at KAP Boy Febrian located at Jalan Tiga Dara Number 3A, RT. 06 RW 03 Kel. Delima, Binawidya District, Pekanbaru City, Riau 28291. Informants in the study were all employees of KAP Boy Febrian. The data in the study used primary data and secondary data. Primary data obtained from interviews with informants, observation and documentation. Secondary data is obtained from previous research data. The results showed that financial statement audit planning at KAP Boy Febrian consisted of eight stages. Each stage must be carried out effectively so that the audit results obtained are of good quality and can be used by interested parties.